Pattern of small hotel businesses: a perspective from the practitioners / Khairil Wahidin Awang ...[et al.] - Awang, Khairil Wahidin; Abdul Aziz, Yuhanis; Samdin, Zaiton (Universiti Teknologi MARA (UiTM), Malaysia, 2011)
Tourism has been depicted as a sector that is dominated by large business establishments. Nevertheless, the participation of the small businesses cannot be simply ignored. Their existence in sheer number indicates their vast influence to the tourism industry, including their contributions to the local economies. This paper aims to elucidate the factors that shape the development of these small businesses. Focus was given to the pattern of ownership. Having insight to this phenomenon could further propel local tourism industry to greater height, in parallel with the Malaysia's notion of growing and sustaining the sector as one of the country's top economic earner. Data from in-depth interviews with owner-managers of small hotels formed the bulk of the arguments. Findings, among others, suggest that although the sector has low entry level, many operators still faced major obstacles in starting or sustaining their operations, thus hindering the potential growth of the sector.